The Failure Reduction in Air Conditioning System in High Rise Building - Manoonphon, Akekasit; Rakkarn, Sakchai; Sriwichian, Podchanee; Plongmai, Jeerawat; laor, Jompop (วารสารวิทยาศาสตร์และเทคโนโลยี สถาบันอุดมศึกษาเอกชนแห่งประเทศไทย, 2023)
This research was to analyze the factors that caused defects in the air conditioning system in high-rise buildings. The objective was to reduce such defects by setting preventive measures and improvements using information from actual operation and repairing reports. Analysis of the risk priority number (RPN) was to find the most important improvements and then using the standard for installing air conditioning systems in high-rise buildings as a guideline, which consisted of Re-design, Preventive Maintenance and Temperature Set Point setting. The results showed that the number of requests for air conditioning repair decreased from 331 times to 145 times or 43.80%, which was a satisfactory ratio in actual reducing the number of repair requests for air conditioning systems in high-rise buildings. Finally the results from the experiment will help machines and equipment to work with maximum efficiency.